Laminin induces the stable expression of surface galactosyltransferase on lamellipodia of migrating cells (The Rockefeller University Press, 1989)
We have previously shown that cell surface galactosyltransferase (GalTase) mediates cell spreading and migration on basal lamina matrices by binding N-linked oligosaccharide substrates within laminin. In this study we have examined the distribution and expression of cell surface GalTase during mesenchymal cell migration on various extracellular matrices. Antisera raised against affinity-purified beta 1,4 GalTase, as well as anti-GalTase Fab fragments, inhibited cell migration on laminin-containing matrices, whereas under identical conditions, anti-GalTase IgG had no effect on the rate of cell migration on fibronectin substrates. Cells migrating on laminin had three times the level of surface GalTase, assayed by 125I-antibody binding and by direct enzyme assay, than similar cells migrating on fibronectin. On the other hand, total cellular GalTase, assayed either enzymatically or by Northern blot analysis, was similar when cells were grown on laminin or fibronectin. The laminin-dependent increase in surface GalTase was due to its expression onto the leading and trailing edges of migrating cells in association with actin-containing microfilaments assayed by double-label indirect immunofluorescence. On stationary cells, surface GalTase levels were low, but as cells began to migrate on laminin GalTase became polarized to the growing lamellipodia. GalTase was not detectable on lamellipodia or filopodia when cells migrated on fibronectin substrates. These results show that laminin-containing matrices induce the stable expression of GalTase onto cell lamellipodia and filopodia where it mediates subsequent cell spreading and migration. Since fibronectin was unable to induce GalTase expression onto lamellipodia, these studies also suggest that the extracellular matrix can selectively influence which intracellular components are maintained on the cell surface.